Water, sanitation, and hygiene factors associated with nutrition status among children under five years in Ewaso Narok Wetland, Laikipia County, Kenya - Kiilu, Colleta M.; P. Oyore, John; Mwanzo, Isaac J. M. (International Journal Of Community Medicine And Public Health, 2024)
Background: Wetlands are known to harbor disease-causing bacteria, posing health risks that can be mitigated through improved water, sanitation, and hygiene (WASH) practices. This study aimed to understand the factors affecting nutritional status and its connection to WASH-related diseases among children under five in Ewaso Narok Wetland, Laikipia County. Methods: Using a mixed-method approach, qualitative and quantitative data were collected. Simple random method was used to identify the respondents. Results: Findings revealed that 36% of households surveyed had children with nutritional edema, with mean age, weight, and height at 21 months, 11 kilograms, and 73 centimeters respectively. Using WHO standards, a significant proportion of children were found to be undernourished at 45.3% and stunted at 41.3%. Socio-demographic factors like caregiver education level and marital status were identified as influential on the nutrition status. While 51% of households had unimproved water sources, 86% had access to toilet facilities, predominantly traditional pit latrines. 67% of the respondents were located near a wetland with a proximity ranging from 1km to 5km. Disease prevalence among children included diarrhea (46%), typhoid-related fevers (22%), and malaria (12%), with edema significantly associated with WASH diseases. Conclusions: Factors such as feces disposal, wetland proximity, protective gear use, handwashing, and toilet facilities were linked to child nutrition. Recommendations include implementing WASH programs, improving water and sanitation access, promoting hygiene practices, ensuring safe feces disposal, using protective gear in wetlands, and advocating for improved toilet facilities. Further research is warranted to assess intervention effectiveness and explore additional influencing factors.